Quiescence Through the Prism of Evolution - Daignan-Fornier, Bertrand; Laporte, Damien; Sagot, Isabelle (Frontiers in Cell and Developmental Biology, 2021)
Being able to reproduce and survive is fundamental to all forms of life. In primitive unicellular organisms, the emergence of quiescence as a reversible proliferation arrest has most likely improved cell survival under unfavorable environmental conditions. During evolution, with the repeated appearances of multicellularity, several aspects of unicellular quiescence were conserved while new quiescent cell intrinsic abilities arose. We propose that the formation of a microenvironment by neighboring cells has allowed disconnecting quiescence from nutritional cues. In this new context, non-proliferative cells can stay metabolically active, potentially authorizing the emergence of new quiescent cell properties, and thereby favoring cell specialization. Through its co-evolution with cell specialization, quiescence may have been a key motor of the fascinating diversity of multicellular complexity.